Linux essentials for cybersecurity lab manual - Rothwell, William (Pearson IT cybersecurity curriculum., 2019)
This lab manual accompanies the textbook Linux Essentials for Cybersecurity, which teaches people how to use Linux systems and ensures that the Linux systems they work on are as secure as possible. To really become a Linux cybersecurity expert, you need practice. In this book, there are three different types of labs to practice your skills: Labs in which you are presented with a short problem that requires only a single operation to complete. Labs that are more complex but in which we provide you with a guide to perform each step, one at a time. Scenario labs in which you are asked to solve a problem entirely on your own. These labs are designed to pose a greater challenge. No matter the type, these labs are designed to be performed on live Linux systems to give you hands-on practice and develop critical thinking and complex problem-solving skills.